Sekuritisasi Presiden Immanuel Macron Terhadap Imigran Muslim Melalui Undang-Undang Anti-Separatisme Perancis - Nida Saidathul Iza; Mohammad Rosyidin; Reni Windiani (Journal of International Relations, 2022)
In response to the issue of Muslim immigrants, a controversial policy has been issued by France. President Immanuel Macron issued a policy to respond to the increasing number of cases of extremism and terrorism in various regions of France and became one of the instruments of regional security. Macron addressed the issue by issuing a speech to shape perceptions of the threat posed by the issue of Muslim immigrants. So that in the end the policies formed by Macron were successfully accepted by the public and officially ratified. It is interesting to study how the political elites in a country shape the perception of an issue so that in the end the issue gets support from the community. This study will analyze this by using the key question "How is French Securitization Against Muslim Immigrants in the Anti-Separatism Law?". This study aims to explain Macron's role in carrying out securitization efforts through speech acts in the French anti-separatism law. The type of research used is the explanatory type. Securitization theory is used in this study to develop an argument about how an issue can be defined by a political elite as a threat to the state. Statements regarding the issue of Muslim immigrants are the focus of analysis in this study. This study argues that Macron has a role in securitizing Muslim immigrants so that the perception of immigrants as a threat to a country can be formed.